Education Reform: The Effects of School Consolidation on Teachers and Teaching - Barter, Barbara G. (Alberta Journal of Educational Research, 2015)
At least as early as the nineteenth century, the two most related approaches to societal improvement have been restructuring and systemic reform. For education, that has meant school closures as well as consolidation of schools and school districts. Although there exists a substantive literature on educational reform there appears to be little discussion on the impact such actions have on schools. This paper briefly describes research on current issues in rural education with a focus on consolidation. The methodology emphasizes teachers’ knowledge of practice and is followed by the findings, which highlight the impact these reforms have on practicing teachers. The argument is made that government reforms have adopted consolidation of schools and districts as a primary strategy for fiscal accountability. This focus singles out economics, while excluding the cultural and social context embedded within schools and central to the communities in which the schools are situated. In this paper, the argument put forth is that consolidation as a single-minded strategy of education reform is an inadequate framework that places teachers’ work and student learning at risk. The accounts of practicing educators speak for using consolidation only where absolutely necessary and maintaining as many small schools as possible. Depuis au moins le 19e siècle, les deux approches visant l’amélioration de la société les plus liées sont la restructuration et la réforme systémique. Dans le domaine dans l’éducation, cela s’est traduit par la fermeture d’écoles et la consolidation d’écoles et de districts scolaires. Malgré la documentation significative portant sur la réforme éducationnelle, peu de discussion semble exister sur l’impact de telles actions sur les écoles. Cet article décrit brièvement la recherche sur les enjeux actuels en éducation rurale et porte une attention particulière à la consolidation. La méthodologie met l’accent sur les connaissances qu’ont les enseignants de la pratique. Les résultats soulignent l’impact de ces réformes sur les enseignants en exercice. On affirme que les réformes gouvernementales ont adopté la consolidation des écoles et des districts comme stratégie principale pour des raisons de responsabilité financière. Cette concentration sur l’économie exclut le contexte culturel et social qu’on retrouve au sein des écoles et qui est intégré aux communautés dans lesquelles se trouvent ces écoles. Cet article maintient que la consolidation comme stratégie résolue en réforme de l’éducation constitue un cadre inadéquat qui met à risque le travail des enseignants et l’apprentissage par les élèves. Les témoignages des enseignants en exercice militent en faveur de maintenir ouvertes autant de petites écoles que possible et de recourir à la consolidation uniquement lorsque cela est absolument nécessaire.